2008
DOI: 10.1172/jci35339
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin-associated protein 1 interacts with Ahi1 to regulate cerebellar and brainstem development in mice

Abstract: Joubert syndrome is an autosomal recessive disorder characterized by congenital malformation of the cerebellum and brainstem, with abnormal decussation in the brain. Mutations in the Abelson helper integration site 1 gene, which encodes the protein AHI1, have been shown to cause Joubert syndrome. In this study, we found that mouse Ahi1 formed a stable complex with huntingtin-associated protein 1 (Hap1), which is critical for neonatal development and involved in intracellular trafficking. Hap1-knockout mice sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
99
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(116 citation statements)
references
References 55 publications
(83 reference statements)
15
99
0
Order By: Relevance
“…Hap1 may regulate the trafficking of microtubule-and membrane-associated protein cargoes in neurons. In this function, Hap1 is thought to promote protein recycling and prevent protein degradation (Rong et al, 2007;Sheng et al, 2008). Interestingly, Hap1 expression appears to be largely limited to neural tissues (Dragatsis et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Hap1 may regulate the trafficking of microtubule-and membrane-associated protein cargoes in neurons. In this function, Hap1 is thought to promote protein recycling and prevent protein degradation (Rong et al, 2007;Sheng et al, 2008). Interestingly, Hap1 expression appears to be largely limited to neural tissues (Dragatsis et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Hap1 was initially recognized for its binding to polyglutamine-expanded huntingtin (Htt), the protein responsible for Huntington's disease (3). Because Hap1 is expressed at various levels in different types of neurons (1,(4)(5)(6)(7)(8), it is likely involved in cell type-specific functions of the brain. For example, Hap1 is abundantly expressed in the hypothalamus, and its expression in the hypothalamus influences the central control of feeding (9); as a direct result, mice lacking Hap1 are malnourished and die in the early postnatal period (5, 10, 11).…”
mentioning
confidence: 99%
“…Many groups have identified that AHI1 mutations are a frequent cause of disease in patients with specific forms of Joubert syndrome (31,32,33), an autosomal recessive neurodevelopmental disorder. Distribution of AHI1 in the embryonic and postembryonic mouse tissues has been reported, and both protein and mRNA studies have shown that AHI1 is highly distributed in several brain areas implicated in feeding and metabolic regulation, including the hypothalamus and nucleus tractus solitarius in the brain stem (31,34,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…However, two recent reports have demonstrated increased expression of AHI1 protein in the hypothalamus of insulin-treated mice, suggesting a role for AHI1 as a putative central regulator for glucose metabolism and energy homeostasis (13,36). Also, one group reported a significant association between variants in the AHI1 gene and BMI in a Caucasian population of type 2 diabetes patients (12).…”
Section: Discussionmentioning
confidence: 99%